Pedagogia, educação especial e educação inclusiva na UNESP: história e trajetória - Fonseca-janes, Cristiane Regina Xavier [UNESP]; Silva Júnior, Celestino Alves Da [UNESP]; Oliveira, Anna Augusta Sampaio De [UNESP] (Editora Autores Associados, 2013)
This article addresses the historical constitution of Pedagogy undergraduate courses and their current proposal for teacher education and for the management of education systems. Another aspect discussed in the text is the constitution of the Pedagogy undergraduate courses at UNESP, the movement of each one, its specificities, relationship with the national trend, political aspects, and also the implications of the national guidelines for training in special education and the inclusive education approach in teacher education. Nowadays, UNESP has six Pedagogy undergraduate courses that are strongly consolidated and active in the Brazilian educational scenario in the area of teaching, research and extension education, and although UNESP has progressed towards conforming the national guidelines, each course has peculiarities in its pedagogical projects. As a result of this and of the history of the FFC in Marília, we found an organization that includes the perspective of an inclusive education.

O presente artigo trata da constituição histórica dos cursos de pedagogia e de sua proposta atual de formação para a docência e para a gestão de sistemas educacionais. Também são discutidos neste trabalho a constituição dos cursos de pedagogia da Universidade Estadual Paulista Julio de Mesquita Filho (UNESP), o movimento de cada um, suas especificidades, a relação com a tendência nacional, os aspectos políticos e ainda as implicações das diretrizes nacionais para a formação em educação especial e a perspectiva de educação inclusiva na formação de professores. Atualmente, a UNESP conta com seis cursos de pedagogia fortemente consolidados e atuantes no cenário educacional brasileiro na área do ensino, da extensão universitária e da pesquisa e, embora tenha caminhado para uma adequação com base nas diretrizes nacionais, cada curso mantém particularidades em seu projeto pedagógico. Em decorrência desse contexto e pela história da Faculdade de Filosofia e Ciências de Marília, encontramos uma organização que contempla a perspectiva de uma educação inclusiva.

Este artículo trata de la constitución histórica de la pedagogía y su actual propuesta de formación de docentes y la gestión de los sistemas educativos. Otro aspecto tratado en el texto es la constitución de los cursos de pedagogía de la Universidade Estadual Paulista Julio Mesquita Filho (UNESP), el movimiento de cada uno, sus características específicas, la relación con la tendencia nacional, los aspectos políticos, y también las implicaciones de las directrices nacionales para la formación en educación especial y el enfoque de educación inclusiva en la formación docente. En la actualidad, la UNESP tiene seis cursos de pedagogía fuertemente consolidados y activos en el escenario brasileño de educación en el área de la enseñanza, la extensión universitaria y de investigación, y aunque haya caminado hacia un ajuste basado en las directrices nacionales, cada curso mantiene sus peculiaridades en sus proyectos pedagógicos. Como resultado de esto y la historia de la Facultad de Filosofía y Ciencias en Marília, encontramos una organización que incluye la perspectiva de una educación inclusiva.
Pedagogía, educación especial y educación inclusiva en la UNESP: historia y trayectoria
Pedagogy, special education and inclusive education at UNESP: history and trajectory
Keywords: curso de pedagogia; Universidade Estadual Paulista; formação de professores; educação inclusiva; pedagogy undergraduate courses; Universidade Estadual Paulista; teacher education; inclusive education